Utility of Tokyo Guidelines 2018 in early laparoscopic cholecystectomy for mild and moderate acute calculus cholecystitis: A retrospective cohort study - Yan, Yong; Hua, Yinggang; Yuan, Wei; Zhu, Xuanjin; Du, Yongliang; Zhu, Shanfei; Wang, Bailin (Frontiers in Surgery, 2023)
Background Tokyo guidelines 2018 (TG18) proposed laparoscopic cholecystectomy (LC) for acute calculus cholecystitis (ACC) irrespective duration of symptoms. This retrospective study assessed the impact of utility of TG18 in early LC for ACC. Methods From 2018 to 2020, sixty-six patients with mild (grade I) and moderate (grade II) ACC undergone early surgery were studied. Subgroup analyses were based on timing of surgery and operation time. Results 32 versus 34 patients operated within versus beyond 7 days since ACC onset. More patients with grade II AAC in beyond 7 days group (P＜0.05). More patients with enlarged gallbladder in within 7 days group (P＜0.05). The duration of symptoms to admission, symptoms to LC, and operation time were longer in beyond 7 days group (P＜0.05). There were no significant differences regarding intraoperative blood loss, conversion to bail-out procedures, complication rate, hospital stay, and cost between the two groups (P>0.05). Longer operation time was significantly associated with duration of symptoms to admission, symptoms to LC and conversion to laparoscopic subtotal cholecystectomy (LSC) (P＜0.05). Conclusion In a subset of carefully selected patients applying TG18 in early LC for mild and moderate ACC results in acceptable clinical outcomes. Standardized safe steps and conversion to LSC in difficult cases are important.